TO THE PROBLEM OF USE OF CONCEPTS «SUPERSTITION» AND «DOUBLE BELIEF» IN HISTORICAL RESEARCH - Савченко, Сергей (SWorldJournal, 2023)
The paper deals with the problem of using such concepts as «superstition» and «dual faith» in modern historical research. The author substantiates the thesis that the problem-free use of these obsolete and semantic vague concepts is counterproductive in t